The association between antibiotic use and outcomes of HCC patients treated with immune checkpoint inhibitors - Zhang, Lilong; Chen, Chen; Chai, Dongqi; Li, Chunlei; Guan, Yongjun; Liu, Li; Kuang, Tianrui; Deng, Wenhong; Wang, Weixing (Frontiers in Immunology, 2022)
Objective: Recently, immune checkpoint inhibitor (ICI) treatment has shown encouraging performance in improving the prognosis of hepatocellular carcinoma (HCC) patients. The gut microbiome plays a vital role in altering the efficacy of ICIs, which may be impacted by antibiotics. The aim of the meta-analysis is to estimate the influence of antibiotic use on the survival of HCC patients treated with ICIs. Methods: The literature review was conducted using databases like PubMed, EMBASE, Cochrane Library, CNKI, WANFANG DATA, VIP, Google Scholar, and ClinicalTrials.gov before May 15, 2022. The primary endpoints were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR). Results: A total of six retrospective studies met the inclusion criteria. 1056 patients were included in the study, of which 352 (33.33%) received antibiotic treatment. The meta-analysis results revealed antibiotic use did not affect the OS (HR: 1.41, 95% CI: 0.96-2.08, P = 0.088) and PFS (HR: 1.21, 95% CI: 0.73-2.00, P = 0.459) in HCC patients treated with ICIs. Besides, the use of antibiotics did not reduce the ORR (OR: 1.06, 95% CI: 0.69-1.64, P = 0.784) and DCR (OR: 0.42, 95% CI: 0.09-2.06, P = 0.286) in HCC patients treated with ICIs. Conclusion: Current evidence reveals that antibiotic use does alter the therapeutic efficacy of ICIs in HCC patients.